Gamma and Beta Oscillations in Human MEG Encode the Contents of Vibrotactile Working Memory - von Lautz, Alexander H.; Herding, Jan; Ludwig, Simon; Nierhaus, Till; Maess, Burkhard; Villringer, Arno; Blankenburg, Felix (Frontiers in Human Neuroscience, 2017)
Ample evidence suggests that oscillations in the beta band represent quantitative information about somatosensory features during stimulus retention. Visual and auditory working memory research, on the other hand, has indicated a predominant role of gamma oscillations for active working memory processing. Here we reconciled these findings by recording whole-head magnetoencephalography during a vibrotactile frequency comparison task. A Braille stimulator presented healthy subjects with a vibration to the left fingertip that was retained in working memory for comparison with a second stimulus presented after a short delay. During this retention interval spectral power in the beta band from the right intraparietal sulcus and inferior frontal gyrus monotonically increased with the to-be-remembered vibrotactile frequency. In contrast, induced gamma power showed the inverse of this pattern and decreased with higher stimulus frequency in the right inferior frontal gyrus. Together, these results expand the previously established role of beta oscillations for somatosensory working memory to the gamma band and give further evidence that quantitative information may be processed in a fronto-parietal network.